Case Management Approach to Overcoming the Violence Against Child - Aulia Regita Dewi Fitriana; Arimurti Kriswibowo (Journal of Economics, Business, and Government Challenges, 2022)
Violence against children causes multidisciplinary impacts, including physical, psychological, social, and spiritual, affecting prolonged trauma. Case management is a strategy for overcoming cases of violence against a child because it does not focus on the individual child only but also on the family. It is carried out by one assistant intensely and in coordination with various institutions according to the child’s needed. This study aims to describe and analyze case management in overcoming victims of violence against the child in UPTD PPA, Sidoarjo Regency. This study used a qualitative approach with data collection techniques through interviews, observation, and documentation. The data analysis technique used is the analysis technique by Miles, Huberman, & Saldana (2014), which includes: data collection, data condensation, data presentation, and concluding and verification. The study results found that case management carried out by UPTD PPA is well. However, they did not succeed yet in reducing the violence against a child. There were still obstacles from individual children or families who did not want to continue the treatment provided.